Determination of Linoleic Acid Oxylipins in Chinese Baijiu Using Ultra-Performance Liquid Chromatography with Quadruple-Time-of-Flight Mass Spectrometry (UPLC-QTOF-MS) and Nuclear Magnetic Resonance (NMR). (22nd September 2019) - Zhao, Tengfei; Chen, Shuang; Li, Huazhong; Xu, Yan
Abstract: Linoleic acid oxylipins may adversely affect the quality of food products. To investigate the presence of linoleic acid oxylipins in Chinese Baijiu (distilled spirits), nine representative samples were analyzed using ultra-performance liquid chromatography coupled with quadruple-time-of-flight mass spectrometry (UPLC-TOF-MS) in the negative electrospray ionization (ESI) mode. For the first time, 12 oxylipins were identified in Baijiu via UPLC-TOF-MS and nuclear magnetic resonance spectroscopy (NMR). Moreover, a rapid and accurate internal standard (IS) quantification method was developed to determine these oxylipins in Baijiu by UPLC coupled with triple-quadrupole mass spectrometry. The method demonstrated acceptable precision, accuracy, and recovery, and was successfully applied to analyze the nine Baijiu samples. The afforded results indicated that in the soy sauce and strong aroma-type Baijiu samples, linoleic acid oxylipin was present in concentrations ranging from 1.27 to 104.90 μg/L; these values were significantly higher than those observed in the light aroma samples ( P < 0.01). This study proposes a quantitation method to monitor and control the linoleic acid oxylipin contents in Baijiu and provides new insights into the lipid metabolites of this distilled spirit.